Pengaruh Electronic Word Of Mouth (E-Wom) Dan Rating Terhadap Keputusan Pembelian Produk Skincare Bening’s Pada Marketplace Shopee Di Kalangan Mahasiswa Kab. Karawang - Putri Widia Ningsih; Citra Savitri Savitri; Syifa Pramudita Faddila (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Technological developments that continue to increase have an impact on people's lifestyles, the majority of people often look for something practical to meet their needs. Consumers want to make decisions quickly, are not bound by space, are not given a lot of time, and need to manifest themselves in cyberspace, which has a direct or indirect impact on consumerbehavior in buying, selling and consuming products through e-commerce. This study aims to examine how the influence of electronic word of mouth (e-WOM) and ratings on purchasing decisions for Bening's skincare products on the Shopee marketplace. This study uses a quantitative method with the Partial Least Square – Structural Equal Model (PLS-SEM) approach. The population in this study were Bening's skincare users on the marketplace marketplace from 20-24 years old with a total of 31,900 then a sample of 395 respondents among students in Kab. Karawang who use Bening's skincare products are aged 20-24 years. The collection of data sources is distributed through questionnaires and analysis tools using SmartPLS 3.0 software. The results of the study, the researchers proved that e-WOM and ratings have a positive and significant effect on purchasing decisions. Then the simultaneous effect of e-WOM and ratings on purchasingdecisions. Keywords: e-WOM, rating, purchase decision, Shopee